Collections in C(sharp) and .NET : working with lists, enumerables, and iterators - McPeak, Jeremy, 1979-; Safari eBooks ([Place of publication not identified] : O'Reilly, 2015)
"In this Collections in C# and .NET training course, expert author Jeremy McPeak will teach you how to use the collection classes in the .NET framework. This course is designed for users that are already familiar with the basic fundamentals of C# and the .NET framework. You will start by learning about attributes, then jump into learning about common collections, including working with arrays, the HashSet, and the SortedSet. From there, Jeremy will teach you how to create your own collection with Collection, bind data with BindingList, and prevent collection modifications with ReadOnlyCollection. Finally, you will learn about concurrent collections and how to write iterators. Once you have completed this computer based training course, you will have gained a solid understanding of what the collection classes are in the .NET framework and how to use them. Working files are included, allowing you to follow along with the author throughout the lessons."--Resource description page.
Presenter, Jeremy McPeak.
Title from title screen (viewed December 1, 2015).
Date of publication from resource description page.
Keywords: C# (Computer program language); Microsoft .NET Framework; Internet programming; Electronic books